Community perception of odors generated by the Wastewater Treatment Plant El Roble-Puntarenas, Costa Rica - Sáenz, Luz Elena (2016)
In Costa Rica, many Wastewater Pumping Stations (WPS) and Wastewater Treatment Plants (WTP) have being implemented. The wastewater, due to its dissolved compounds together with the decomposition process in which it is involved, produces strong odors (or bad odor) affecting the comfort and life quality of the citizens closer to plant sites. Despite this, during the design and construction process, appropriate mitigation actions have not been included. In order to evaluate the properties of these gases in the environments, there is olfactometry equipment available, however, it is an expensive technique. Considering the sensory capacity, a method was developed by the application of surveys in order to identify the influence radius and other characteristics of the odors generated in El Roble-Puntarenas WTP. This WTP is considered a critical point owing to its influences in tourism services. In total, 256 surveys were made within a radius of 800 m. 76% of the surveys indicated that the odors emitted by the WTP were perceived within a radius of 600m, where 57% of the surveyees indicated that they perceived strong odors and 83% perceived fecal like odors. The time-slots in which the odors were perceived more intensely were from 6:00 to 9:00, 15:00 to 21:00. Likewise, more odors were perceived during the rainy season.